Diagnosis and treatment of periprosthetic infection after hip replacement (a review) - I. A. Dmitrov; N. V. Zagorodniy; V. N. Obolenskiy; P. Sh. Leval'; N. G. Zakharyan; V. S. Apresyan; M. A. Panin; D. A. Samkovich; R. N. Aliev; A. A. Grigoryan (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Introduction. The frequency of hip arthroplasty is steadily increasing throughout the world and, although this operation has become routine, the likelihood of postoperative complications reaches 4.3 % [1]. The most dangerous of them are infectious lesions in the area of the endoprosthesis and adjacent tissues. At the same time, in addition to the threat of generalization of the infectious process, there are functional disorders in the joint area and a general deterioration in the quality of life of the patient. Timely diagnosis and treatment of the infectious process and related disorders can minimize the adverse effects of infection.Target. The purpose of this review is to analyze modern methods for diagnosing and treating periprosthetic infection resulting from hip replacement.Materials and methods. The subject literature was searched using the PubMed and Google Sholar databases.Results. The main methods for diagnosing periprosthetic infection include histological and bacteriological examination of the biopsy specimen, determination of sensitivity to antibiotics, blood, and synovial fluid analysis for the content of leukocytes, IL-6, CRP, PCR diagnostics of infectious agents. Treatment consists of re-intervention and/or antibiotic therapy.Conclusion. The most optimal method for diagnosing periprosthetic infection is a bacteriological study of biopsy specimens taken intraoperatively. The preferred method of treatment is determined by the severity of the infection, the degree of involvement of tissues adjacent to the prosthesis, the comorbid background, the nature of the infectious agent, and includes repeated revision surgery.